Improving Students' Listening Ability Using Edpuzzle Interactive Video - Nadrotin Mawaddah; Mutmainnah Mustofa; Irfan Susiyana Putra (Universitas Muhammadiyah Metro, 2022)
The problems faced by the students in this listening class were identified as the difficulty of recalling memory and managing concentration during listening. Therefore, this classroom action research solution is Edpuzzle interactive video because the teacher can easily embed questions, notes, and recording voices into the video. When students play the video until it reaches a particular minute of the timeline, it will automatically pause, and a question will appear. This study revealed that this media could increase the students' listening skills. The students were more motivated to listen using Edpuzzle because they liked the